How online trust evolves over time: The role of social perception. Issue 11 (18th August 2020) - Ye, Christine; Hofacker, Charles F.; Peloza, John; Allen, Alexis
Abstract: Using customer service scenarios in an online retail context, the current study examines how cognitive and affective trust develop over time and how service failure negatively impacts trust, along with the trust restoration opportunities provided by recovery. Study 1 findings reveal that the relationship between Web site social perception and affective trust is stronger for repeat visitors than for first‐time visitors. Study 2 findings indicate that failure timing and recovery duration play important roles in service failure situations. Overall, the results demonstrate that consumer cognitive and affective trust develop through the number of interactions with a retail Web site over time and that increased Web site social perceptions facilitate the trust‐building process.